A simple and cost effective technique for construction of tissue microarrays (Journal of Pathology of Nepal, 2018)
Background: Tissue microarray is widely used in histopathology and biomedical research. Construction of tissue microarray can help institutes to considerably reduce, cost of consumables, skilled man power needed and time needed in performing high output research. However resource poor centers in developing countries have hardly any access to such techniques.  The aim of this research is to develop simple, cost effective technique for making tissue microarray.Materials and methods: Materials available in a standard pathology laboratory such as skin punch biopsy needle, bone marrow aspiration needle, trephine biopsy needle, stylet, paraffin wax, hot air oven, slide warming table, drawing pin and measuring scale were used in developing this tissue microarray. The tissue array thus developed was sectioned using a standard microtome. Immunohistochemical studies were also performed on these tissue array sections which yielded satisfactory results.Results: This technique for construction of TMAs is simple and cost effective. When 3.5 to 3mm cores were used we were able to construct arrays up to 32 cores in one block. When 1mm cores were used we were able to construct arrays with 100 representative cores in one block. Morphological identification, histological typing and grading could be done in TMA sectionsConclusion: Tissue microarray is a relatively recent innovation in the field of pathology. We hope that our technique will encourage the younger researchers to take up research projects of large sample size requiring molecular studies with significantly lesser economic burden and thus leading to a significant acceleration in the transition of basic research findings into clinical applications.